A systematic drug repurposing approach to identify promising inhibitors from FDA-approved drugs against Nsp4 protein of SARS-CoV-2. Issue 2 (22nd January 2023) - Chakraborty, Joydeep; Maity, Atanu; Sarkar, Hironmoy
Abstract: COVID-19 is caused by SARS-CoV-2 and responsible for the ongoing global pandemic in the world. After more than a year, we are still in lurch to combat and control the situation. Therefore, new therapeutic options to control the ongoing COVID-19 are urgently in need. In our study, we found that nonstructural protein 4 (Nsp4) of SARS-CoV-2 could be a potential target for drug repurposing. Due to availability of only the crystal structure of C-terminal domain of Nsp4 (Ct-Nsp4) and its crucial participation in viral RNA synthesis, we have chosen Ct-Nsp4 as a target for screening the 1600 FDA-approved drugs using molecular docking. Top 102 drugs were found to have the binding energy equal or less than –7.0 kcal/mol. Eribulin and Suvorexant were identified as the two most promising drug molecules based on the docking score. The dynamics of Ct-Nsp4-drug binding was monitored using 100 ns molecular dynamics simulations. From binding free energy calculation over the simulation, both the drugs were found to have considerable binding energy. The present study has identified Eribulin and Suvorexant as promising drug candidates. This finding will be helpful to accelerate the drug discovery process against COVID-19 disease. Communicated by Ramaswamy H. Sarma